Seeing ourselves : women's self-portraits - Borzello, Frances (London : Thames & Hudson, 2016)
This richly diverse exploration of female artists and self-portraits is a brilliant and poignant demonstration of originality in works of haunting variety. The two earliest self-portraits come from 12th-century illuminated manuscripts in which nuns gaze at us across eight centuries. In 16th-century Italy, Sofonisba Anguissola paints one of the longest series of self-portraits, spanning adolescence to old age. In 17th-century Holland, Judith Leyster shows herself at the easel as a relaxed, self-assured professional. In the 18th century, artists from Elisabeth Vigee-Lebrun to Angelica Kauffman express both passion for their craft and the idea of femininity; and in the 19th the salons and art schools at last open their doors to a host of talented women artists, including Berthe Morisot, ushering in a new and resonant self-confidence. The modern period demolishes taboos: Alice Neel painting herself nude at eighty, Frida Kahlo rendering physical pain, Cindy Sherman exploring identity, Marlene Dumas dispensing with all boundaries. The full verve of Frances Borzello's enthralling text, and the hypnotic intensity of the accompanying self-portraits, is revealed to the full in a completely revised edition of this inspiring book.
Machine generated contents note: 1. Sixteenth Century -- In the beginning -- 2. Seventeenth Century -- new self-confidence -- 3. Eighteenth Century -- Professionals and amateurs -- 4. Nineteenth Century -- opening door -- 5. Twentieth Century -- Breaking taboos -- 6. Into the Future -- feminist impact.
Originally published : London : Thames and Hudson, 1998.
Includes bibliographical references and index.
Keywords: Women artists; Women artists -- Psychology; Women artists -- Portraits; Self-perception in women; Self-portraits.; Femmes artistes; Femmes artistes -- Psychologie; Femmes artistes -- Portraits; Perception de soi chez la femme; Autoportraits